The practice of enterprise modeling : 12th IFIP Working Conference, PoEM 2019, Luxembourg, Luxembourg, November 27-29, 2019, proceedings /: 12th IFIP Working Conference, PoEM 2019, Luxembourg, Luxembourg, November 27-29, 2019, proceedings. ([2019]) - Unknown
No abstract available